Systematic studies in the genus Phlox (polemoniaceae): cytotypic variation in Phlox nana nutt. and utility of a low copy nuclear gene region (IDHB) for phylogeny development - Wright, Bethany Ann (Kansas State University, 2014)
The genus Phlox L. presents intriguing opportunities for systematics research, and P. nana is of particular interest. Phlox nana occurs chiefly in mountains of the Chihuahuan desert to northern New Mexico, and it exhibits much morphological variation across its range. Historically, this taxon has been recognized as a single species (sometimes with infraspecific taxa), or as several species. Perhaps most interesting, variation in ploidy level (cytotypic variation) has been evidenced for P. nana. This research employed flow cytometry methods in conjunction with chromosome counts to document patterns of cytotypic variation. Intensive fieldwork in Arizona, New Mexico and Texas enabled excellent sampling, and evaluation of ploidy level for 76 populations was achieved. Diploid and tetraploid chromosome counts were made (four diploid counts; five tetraploid counts), and flow cytometry was conducted on all populations, providing evidence for diploid, tetraploid and hexaploid populations. Polyploids were found to occur in many geographical areas, and in some regions, diploids and polyploids occur in close geographical proximity (e.g., within both the Davis Mountains and the Chisos Mountains of west Texas). Genome size data are presented (with discussion of unusual populations), and geographic patterns of cytotypic variation are presented and discussed. Patterns are also briefly considered with respect to morphology and taxonomy: cytotypic variation does not readily align with historical recognition of taxonomic variation, and this work sets the stage for ongoing, detailed morphometric study. Research on particular species of Phlox benefits from an understanding of a broad phylogenetic context, and low copy nuclear DNA regions are an important resource for phylogeny development. This research further evaluated part of the NADP-dependent isocitrate dehydrogenase gene (idhB) for its usefulness in inferring relationships in Phlox. Samples were PCR amplified for idhB and cloned, and resulting sequences were added to a larger set of idhB sequence data previously developed in the lab. A total of 163 samples were included, and Bayesian Inference and Maximum Parsimony analyses were conducted for complete data sets. Phylogenetic findings are discussed in light of previous work based on chloroplast and high copy nuclear DNA regions, and challenges and utility of using idhB are discussed.
Keywords: Phlox nana; Phlox; Plant systematics; Phylogenetics; Biology (0306); Plant Biology (0309); Systematic biology (0423)